Reducing oral flora contamination of intravitreal injections with face mask or silence - Doshi, Rishi R; Leng, Theodore; Fung, Anne E (Retina (Philadelphia, Pa.), 2012)
To provide experimental evidence to support or refute the proposition that the use of surgical face masks and/or avoidance of talking can decrease the dispersion of respiratory flora during an intravitreal injection. Ten surgeons recited a 30-second standardized script with blood agar plates positioned 30 cm below their mouths. The plates were divided into 4 groups, with 10 plates per group. In Group 1, participants did not wear a face mask. In Group 2, participants wore a standard surgical mask. In Group 3, no mask was worn, but plates were pretreated with 5% povidone-iodine. In Group 4, no mask was worn, and participants remained silent for 30 seconds. The plates were then incubated at 37°C for 24 hours, and the number of colony-forming units (CFUs) was determined. Mean bacterial growth were as follows: Group 1, 8.6 CFUs per subject; Group 2, 1.1 CFUs per subject; Group 3, 0.1 CFUs per subject; and Group 4, 2.4 CFUs per subject. Differences between the groups were statistically significant (P < 0.05), with the exception of Group 2 versus Group 4 (P = 0.115). The use of a face mask and avoidance of talking each significantly decreased the dispersion of bacteria. Even without these interventions, plates pretreated with povidone-iodine demonstrated the least bacterial growth.